(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the present study, Structural, UV spectroscopic properties and quantum chemical calculations have been performed on theoretical study of the diphenyl-diketopyrrolopyrrole with its derivatives (chlorodiphenyl-diketopyrrolopyrrole, bromodiphenyl-diketopyrrolopyrrole and fluorodiphenyl-diketopyrrolopyrrole) were studied.Using the DFT/B3LYP/6-311G (d,p) level of theory in the gas phase, the compounds’ ground state geometries have been optimised. The assigned chemical structure of molecules was confirmed using IR spectroscopic technique. The UV-Vis spectral properties, maximum wavelength, energy and oscillator strength of three compounds were predicted by the TD-DFT approach. The extracted molecular structure has served as the basis for geometric optimisations. The structural and geometric characteristics were computed, and theoretical results were compared to experimental X-ray values obtained from the literature. The computationally calculated structural and geometric characteristics correlate well with the experimentally acquired x-ray values that documented from literature. The effects of the halogen substituent on the characteristic diphenyl-diketopyrrolopyrrole bands in the UV-visible spectral are discussed. In addition, Chemical reactivity descriptors on a global scale, such as frontier molecular orbital analysis, were used to the compounds’ optimal structures in order to address their reactive qualities.